2011
DOI: 10.1371/journal.pone.0016712
|View full text |Cite
|
Sign up to set email alerts
|

Anti-Angiogenic and Anti-Inflammatory Effects of SERPINA3K on Corneal Injury

Abstract: SERPINA3K is a member of the serine proteinase inhibitor (SERPIN) family. Here we evaluated the therapeutic effects of SERPINA3K on neovascularization and inflammation in a rat cornea alkali burn model that is commonly employed to study corneal wounding. Topical treatment of the injured rat cornea with SERPINA3K (20 µg/eye/day) for 7 days significantly decreased the neovascular area, compared with the groups treated with BSA or PBS. The SERPINA3K treatment also ameliorated the corneal inflammation as evaluated… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
61
0
6

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 54 publications
(68 citation statements)
references
References 35 publications
1
61
0
6
Order By: Relevance
“…86 Netrin-1 ve 4 ile SERPINA3K'de kombine etkili tedavi sağlayan yeni ajanlardandır. 87,88 Doğal bir antianjiyojenik faktör olan PEDF sekresyonunu artırır ve VEGF sekresyonunu baskılar. 89 Han ve ark.nın çalışmasında, alkali yanık modelinde 10 gün sonra başlanan netrin-1'in korneal NV'yi engellediği, antiapoptotik, antiinflamatuar etkilerinin olduğu ve epitel iyileşmesini hızlandırdığı gösteril-miştir.…”
Section: Vegf Dışındaki Anjiyogenez Stratejileriunclassified
“…86 Netrin-1 ve 4 ile SERPINA3K'de kombine etkili tedavi sağlayan yeni ajanlardandır. 87,88 Doğal bir antianjiyojenik faktör olan PEDF sekresyonunu artırır ve VEGF sekresyonunu baskılar. 89 Han ve ark.nın çalışmasında, alkali yanık modelinde 10 gün sonra başlanan netrin-1'in korneal NV'yi engellediği, antiapoptotik, antiinflamatuar etkilerinin olduğu ve epitel iyileşmesini hızlandırdığı gösteril-miştir.…”
Section: Vegf Dışındaki Anjiyogenez Stratejileriunclassified
“…A similar study evaluated the effects of SERPINA3K, a natural antiangiogenic protein, 48 on corneal angiogenesis. Similar to the experiment described above, mice were subjected to an alkali burn and then treated with either a PBS control or SERPINA3K eye drop solution.…”
Section: Non-vegf Treatmentsmentioning
confidence: 99%
“…Eight days after alkali burn, the area of corneal NV was smaller in mice treated with SERPINA3K, and the cornea appeared more transparent and with less edema compared to control mice. 48 A Western blot analysis of the cornea performed 8 days after alkali burn showed that mice treated with the SERPINA3K expressed much lower levels of VEGF and higher levels of PEDF. 48 From these data, it is clear that netrin-1 and SER-PINA3K are two factors that show considerable promise in the inhibition of corneal angiogenesis.…”
Section: Non-vegf Treatmentsmentioning
confidence: 99%
“…Experimental corneal NV allows the clear visualization of abnormal vascular growth and shows no natural regression, making this an attractive model in which to study vessel regression. The corneal alkali burn model is a well-established model of corneal NV, corneal epithelial defects, prominent corneal inflammation, and reduced corneal transparency [2,3]. It is widely used to study the mechanism of and investigate therapies for inflammation and angiogenesis, due to well accessible position for observation, and the relatively immune-privileged status of the cornea.…”
Section: Introductionmentioning
confidence: 99%